2014
DOI: 10.1002/jcla.21691
|View full text |Cite
|
Sign up to set email alerts
|

Performance Evaluation of Platelet Counting by Novel Fluorescent Dye Staining in the XN-Series Automated Hematology Analyzers

Abstract: The platelet counting performance of the PLT-F channel of the XN Series had improved accuracy and precision in the low range and in abnormal samples, avoiding the interference by nonplatelet particles.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
42
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(46 citation statements)
references
References 9 publications
(11 reference statements)
3
42
0
1
Order By: Relevance
“…Tanaka et al published data on the stability of the PLT count, 22 which are overall similar to the results observed in this study (PLT seem to be stable for up to 48 h in blood samples stored at both RT and at 4 °C). Discrepant data were instead found comparing our results with those obtained by Daves et al 23 and by Imeri et al 2 using the Sysmex XN-series.…”
Section: Discussionsupporting
confidence: 90%
“…Tanaka et al published data on the stability of the PLT count, 22 which are overall similar to the results observed in this study (PLT seem to be stable for up to 48 h in blood samples stored at both RT and at 4 °C). Discrepant data were instead found comparing our results with those obtained by Daves et al 23 and by Imeri et al 2 using the Sysmex XN-series.…”
Section: Discussionsupporting
confidence: 90%
“…Tanaka et al . and Schoorl et al . demonstrated improved accuracy and imprecision of fluorescence platelets in the low range.…”
Section: Discussionmentioning
confidence: 92%
“…When fluorescence platelets (Plt-F) are available, as is the case in our laboratory, verification of a severe thrombocytopenia could aid in decision-making. Tanaka et al [10] and Schoorl et al [11] demonstrated improved accuracy and imprecision of fluorescence platelets in the low range. Briggs et al [12] reported a CV of 4%, Plt-F, for low platelet counts (<39 9 10 9 /L).…”
Section: Discussionmentioning
confidence: 99%
“…Sakuragi et al [12] suggested in their study that IPF% was comparable to reticulated platelets measured by flow cytometry; it was considered as a supportive diagnostic test discriminating disorders such as ITP and aplastic anemia.…”
Section: Discussionmentioning
confidence: 98%
“…A high %-IPF indicates either consumptive or recovering thrombocytopenic disorders, such as immune thrombocytopenic purpura, while low %-IPF is characteristic of bone marrow suppression states [10,12].…”
Section: Introductionmentioning
confidence: 99%